Mekanisme Pasar dalam Islam - Rahmi, Ain (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The market mechanism will be reflected in the concept of Islamic Shari'ah principles in the formof values which can generally be divided into two perspectives: macro and micro. Shari'ah valuesin a micro perspective emphasizes the aspects of competence/professionalism and attitude oftrust, while the macro perspective Shari'ah values emphasize aspects of the distribution, theprohibition of usury and economic activities that do not provide real benefits to the economy.Therefore, it can be seen clearly benefit the Islamic economic system in the market thataddressed not only to the citizens of the Islamic community, but to all human being (rahmatanlil"™Ä€lamÃn).